Reimagining the Higher Education Student Constructing and Contesting Identities - Brooks, Rachel; O'Shea, Sarah (Research into Higher Education, 2021)
Drawing on the perspectives of scholars and researchers from around the world, this book challenges dominant constructions of higher education students. Given the increasing number and diversity of such students, the book offers a timely discussion of the implicit and sometimes subtle ways that they are characterised or defined. Topics vary from the ways that curriculum designers 'imagine' learners, the complex and evolving nature of student identity work, through to newspaper and TV representations of university attendees. Reimagining the Higher Education Student seeks to question the accepted or unquestioned nature of 'being a student' and instead foreground the contradictions and 'messiness' of such ideation. Offering timely insights into the nature of the student experience and providing an understanding of what students may desire from their Higher Education participation, this book covers a range of issues, including: Impressions versus the reality of being a Higher Education student Portrayals of students in various media including newspapers, TV shows and online Generational perspectives on students, and students as family members Itis a valuable resource for academics and students both researching and working in higher education, especially those with a focus on identities, their importance and their constructions.